"Metal‐Free" Catalytic Oxygen Reduction Reaction on Heteroatom‐Doped Graphene is Caused by Trace Metal Impurities1. (25th November 2013) - Wang, Lu; Ambrosi, Adriano; Pumera, Martin
Abstract The oxygen reduction reaction (ORR) is of high industrial importance. There is a large body of literature showing that metal‐based catalytic nanoparticles (e.g. Co, Mn, Fe or hybrid Mn/Co‐based nanoparticles) supported on graphene act as efficient catalysts for the ORR. A significant research effort is also directed to the so‐called "metal‐free" oxygen reduction reaction on heteroatom‐doped graphene surfaces. While such studies of the ORR on nonmetallic heteroatom‐doped graphene are advertised as "metal‐free" there is typically no sufficient effort to characterize the doped materials to verify that they are indeed free of any trace metal. Here we argue that the claimed "metal‐free" electrocatalysis of the oxygen reduction reaction on heteroatom‐doped graphene is caused by metallic impurities present within the graphene materials.